Novel wine in an old bottle: Preventive and therapeutic potentials of andrographolide in atherosclerotic cardiovascular diseases - Tingting Gou; Minghao Hu; Min Xu; Yuchen Chen; Rong Chen; Tao Zhou; Junjing Liu; Li Guo; Hui Ao; Qiang Ye (Elsevier, 2023)
Atherosclerotic cardiovascular disease (ASCVD) frequently results in sudden death and poses a serious threat to public health worldwide. The drugs approved for the prevention and treatment of ASCVD are usually used in combination but are inefficient owing to their side effects and single therapeutic targets. Therefore, the use of natural products in developing drugs for the prevention and treatment of ASCVD has received great scholarly attention. Andrographolide (AG) is a diterpenoid lactone compound extracted from Andrographis paniculata. In addition to its use in conditions such as sore throat, AG can be used to prevent and treat ASCVD. It is different from drugs that are commonly used in the prevention and treatment of ASCVD and can not only treat obesity, diabetes, hyperlipidaemia and ASCVD but also inhibit the pathological process of atherosclerosis (AS) including lipid accumulation, inflammation, oxidative stress and cellular abnormalities by regulating various targets and pathways. However, the pharmacological mechanisms of AG underlying the prevention and treatment of ASCVD have not been corroborated, which may hinder its clinical development and application. Therefore, this review summarizes the physiological and pathological mechanisms underlying the development of ASCVD and the in vivo and in vitro pharmacological effects of AG on the relative risk factors of AS and ASCVD. The findings support the use of the old pharmacological compound ('old bottle') as a novel drug ('novel wine') for the prevention and treatment of ASCVD. Additionally, this review summarizes studies on the availability as well as pharmaceutical and pharmacokinetic properties of AG, aiming to provide more information regarding the clinical application and further research and development of AG.